ZBTB16-RARα variant of acute promyelocytic leukemia with tuberculosis: a case report and review of literature - Palta, Anshu (Korean Society of Hematology; Korean Society of Blood and Marrow Transplantation; Korean Society of Pediatric Hematology-Oncology; Korean Society on Thrombosis and Hemostasis, 2012)
A 23-year-old male presented with pulmonary tuberculosis and swelling of both lower limbs. He was put on antitubercular treatment. Hemogram showed mild anemia and Pseudo Pelger-huet cells. The bone marrow (BM) examination showed 52% promyelocytes with regular round to oval nuclei, few granules and were positive for CD13 and CD33, and negative for HLA-DR. Cytogenetic analysis of the BM aspirate revealed an apparently balanced t(11;17)(q23;q21). Final diagnosis rendered was acute promyelocytic leukemia (APL) with t(11;17)(q23;q21); ZBTB16/RARA. APL is a distinct subtype of acute myeloid leukemia. The variant APL with t(11;17)(q23;q21) cases that are associated with the ZBTB16/RARA fusion gene have been reported as being resistant to all-trans-retinoic acid (ATRA). Therefore, differential diagnosis of variant APL with t(11;17)(q23;q12) from classical APL with t(15;17)(q22;q12); PML-RARA is very important. Here we have discussed the importance of distinct morphology of variant APL and also significance of rare presentation with tuberculosis.